Rhodamine-alginate conjugate as self-indicating gel beads for efficient detection and scavenging of Hg 2+ and Cr 3+ in aqueous media - Saha, Sukdeb; Chhatbar, Mahesh U.; Mahato, Prasenjit; Praveen, L.; Siddhanta, A. K.; Das, Amitava (Chemical Communications, 2012)
Effective extraction of Hg2+ and Cr3+ ions from aqueous media by novel rhodamine–alginate polymer-based highly fluorogenic, as well as colorimetric, chemosensor beads.